2017
DOI: 10.1111/ijcp.12957
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Vitamin D supplementation on hormonal and glycaemic profile of patients with PCOS: A meta-analysis of randomised trials

Abstract: There is no evidence to support that vitamin D supplementation significantly benefits PCOS patients. However, given the relatively small number of enrolled patients further studies are needed to elucidate this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Seven reviews evaluated vitamin D (Appendix S3, found in the Supporting Information) either as monotherapy vs placebo or metformin, as combination therapy with metformin vs metformin or comparing the effects of before and after vitamin D. Only one review had a high rating while the majority of the reviews (n = 5) were of moderate quality, and one review was of low quality. A total of 75 trials and 5701 participants women with PCOS were involved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven reviews evaluated vitamin D (Appendix S3, found in the Supporting Information) either as monotherapy vs placebo or metformin, as combination therapy with metformin vs metformin or comparing the effects of before and after vitamin D. Only one review had a high rating while the majority of the reviews (n = 5) were of moderate quality, and one review was of low quality. A total of 75 trials and 5701 participants women with PCOS were involved.…”
Section: Resultsmentioning
confidence: 99%
“…Five reviews assessed endocrine outcomes with 2 reviews reporting benefits DHEAS (n = 1 comparing vitamin D vs placebo and vitamin D with metformin vs metformin) or testosterone (n = 1 comparing vitamin D vs placebo) . Metabolic outcomes were assessed by 6 reviews with 4 reviews reported benefits as reductions in HOMA‐IR (n = 1 comparing vitamin D vs placebo or combination therapy vs metformin), total cholesterol (n = 1 comparing vitamin D vs placebo) or triglycerides (n = 2 comparing before and after vitamin D) . One review reported significant improvements in blood pressure for vitamin D vs placebo .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations